Optometrist: the missing profession in Thai vision care services - Parsuraphun, Ploychompoo; Ausayakhun, Somsanguan (Biomedical Sciences and Clinical Medicine, 2018)
Optometrist is one profession that has not broadly introduced in Thai medical profession. Their primary roles are to perform refractive error examination, diagnosis and treat vision disorder by applying spectacle lenses, contact lenses and other medical instruments. They also provide preliminary vision care by screening ocular health and may referring to ophthalmologists if a severe ocular disease is found. They also co-operate ophthalmologists by advising patients about their vision problems before and after eye surgery. Licensed Thai-optometrists must complete a doctor of optometry degree for six academic years and pass optometry board examination. The increasing number of optometrists will fulfill shortage of eye healthcare professionals and help Thai people to have a better vision and quality of life.